2022
DOI: 10.1111/jopr.13578
|View full text |Cite
|
Sign up to set email alerts
|

Perception of orbital epitheses evaluated with eye tracker

Abstract: Purpose Orbital epitheses replace a missing eyeball and surrounding soft tissue. Perception of epithesis in public gaze and the attention areas on the face are of interest. This study aimed to examine the differences in perception of orbital epitheses by prosthodontists, dentistry students, and laypeople with an objective evaluation tool that utilized eye‐tracking technology. Materials and methods Twenty‐four frontal facial images of 12 patients who had orbital epitheses were viewed by 81 observers (prosthodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Eye tracking can be used to analyze one's perception and attention by monitoring eye movements to yield objective qualitative and quantitative data, such as eye movements, the location of the observer's viewpoint, and the duration of the fixation on each location. 33,34 Second, eye tracking can help patients to evaluate objectively the social aspects of their dento-maxillofacial deformities before treatment or to compare their deformities with those of healthy individuals without the condition. This application of eye tracking makes it a useful tool for counseling persons with disfigurements to determine whether the patient's defect is visually distracting in the first place, quantify this distraction, and illustrate the necessity to improve or normalize an observer's perception of the corresponding area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eye tracking can be used to analyze one's perception and attention by monitoring eye movements to yield objective qualitative and quantitative data, such as eye movements, the location of the observer's viewpoint, and the duration of the fixation on each location. 33,34 Second, eye tracking can help patients to evaluate objectively the social aspects of their dento-maxillofacial deformities before treatment or to compare their deformities with those of healthy individuals without the condition. This application of eye tracking makes it a useful tool for counseling persons with disfigurements to determine whether the patient's defect is visually distracting in the first place, quantify this distraction, and illustrate the necessity to improve or normalize an observer's perception of the corresponding area.…”
Section: Discussionmentioning
confidence: 99%
“…47 Some studies have focused on whether there are significant differences in the ways that different classes of observers perceive changes in facial profiles or malocclusions. Basmacı et al 33 found that prosthodontists paid more attention to the mouth and eye regions in symmetrical images than laypeople did. Fujii et al 48 found that the durations of eye fixation on the nose tip and upper lip in a dental-education group were longer than the durations observed in a nodental-education group while perceiving facial profile images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation